Local Community-Based Tourism Development in Batu Cermin Tourism Village, West Manggarai Regency - Andriano Calrinto Mami; Nyoman Ariana; I Putu Anom (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Community empowerment is one of the main elements in the process of developing a tourist village. One proof of empowerment is the participation of the community in the tourism development process. This study aims to identify internal and external factors in the tourism development process in Batu Cermin Tourism Village. Furthermore, it formulates appropriate strategies for community-based tourism development in Batu Cermin Tourism Village, West Manggarai Regency. This research uses a qualitative method approach. The data sources in this study were obtained through observation, interviews, literature studies, documentation, and the distribution of questionnaires. Subsequently, the obtained data were analysed using qualitative descriptive analysis, IFE and EFE analysis, IE matrix, SWOT matrix, and Quantitative Strategic Planning Matrix (QSPM) analysis. The research results show that the main strength factor is the strategic location of Batu Cermin Tourism Village, while the main weakness is the suboptimal collaboration among stakeholders. Furthermore, enhancing the knowledge of the local community becomes the main opportunity factor for Batu Cermin Tourism Village in the tourism development process, and the main threat factor is regulation. Based on the SWOT analysis results, seven strategies are proposed: optimising destination promotion, improving the quality of tourism human resources, maximising local community participation in destination development, optimising destination management, disaster mitigation and preventive measures, maximising synergy among tourism stakeholders in the destination, and establishing cooperation among destinations in Labuan Bajo. Maximising synergy among tourism stakeholders in the destination is the priority strategy based on the QSPM analysis results.